The relative importance of personal beliefs, meta-stereotypes and societal stereotypes of age for the wellbeing of older people - Fasel, N.; Vauclair, C.-M.; Lima, M. L.; Abrams, D. (Ageing and Society, 2021)
Negative images of old age can harm older individuals' cognitive and physical functioning and health. Yet, older people may be confronted with age stereotypes that are inconsistent with their own personal beliefs. We examine the implications for older people's wellbeing of three distinct elements of age stereotypes: their personal beliefs about their age group, their perception about how others generally perceive older people (i.e. their meta-stereotypes) and the societal age stereotypes that are empirically widely shared in society. Using measures from the Stereotype Content Model and survey data of older people from the United Kingdom (UK) (Study 1, N = 171), we found only partial overlap between older people's personal beliefs and their meta-stereotypes. Personal beliefs were unrelated to wellbeing, but positive meta-stereotypes of older people's competence were linked to higher wellbeing. These findings were largely replicated with a sample of baby-boomers from Switzerland (Study 2, N = 400) controlling for socio-demographics. Study 3 used representative survey data (N = 10,803) across 29 European countries, to test and confirm that the link between positive competence meta-stereotypes and wellbeing can be generalised to different cultures, and that positive warmth meta-stereotypes were an additional predictor. At the country level, societal age stereotypes about competence were positively related to the wellbeing of older people, but only in countries that provide greater opportunities for competence attainment.